THE ROLE OF THE DENTIST IN CARING FOR PATIENTS WITH Cleft Lip and Palate: A LITERATURE REVIEW - Durando Rebouças, Beatriz; Luzia Coelho Bezerra de Carvalho, Isabela; Jamille de Moura Feitosa, Júlia; Jordania Lino Figueredo, Lívia; Guerra de Mendonça, Igor; Suammi Lima de Carvalho, Ilana; Alves Freitas Cruz, Kádja; Rodrigues Silva, Nicole; de Souza Pereira, Malvina; Gabriel Gomes Rodrigues, Thalys (Health and Society, 2025)
Introduction: Cleft lip and palate are innate deformities in the anatomical fusion of facial processes. Objective: This literature review aims to highlight the relevance of the team of health professionals in providing a better quality of life to the patient. Methodology: The databases used were Pubmed and SciElo, in English, Portuguese and Spanish. Fifty-six articles were analyzed, of which only 13 met the inclusion criteria. Results: Since it is an opening in the lip and/or palate region, with multifactorial etiology presenting several consequences, dental follow-up is guided by the complexity of the cases. Conclusion: The dentist plays an essential role throughout the patient’s life, acting in both therapeutic and preventive ways, ensuring a comprehensive approach that includes functional, emotional and social aspects. Integration among health professionals is essential for effective rehabilitation and for improving the quality of life of these patients.